The role of Phosphate Fertilization on physiological responses of the young Bertholletia excelsa plants grown in a P-Deficient amazon ferralsol - Corrêa, Viviane; Gonçalves, José; Costa, Karen; Oliveira, Igor; Santos, José; Oliveira, Sabrina; Ferreira, Marciel; Lima, Roberval; Araújo, Wagner; Nunes-Nesi, Adriano (Plants, 2022)
Phosphorus (P) reacts with soil minerals, which makes it less available to plants. Considering that Amazonian soils have a low pH and nutrient availability, both of these properties contribute to an increase in P limitation. Here, we investigate how the addition of P to the substrate affects morpho-physiological traits of Brazil nut trees (Bertholletia excelsa Bonpl.). The experiment was carried out in a greenhouse with 24-month-old saplings, and the P treatments consisted of a control (Ferrasol without P addition) and 100, 200, 400, and 500 mg P kg−1 of added to the soil. When B. excelsa saplings were fertilized with phosphate, the N:P leaf ratio reduced from 50 to 26. Addition of P favored the photochemical efficiency of PSII (FV/FM), and the application of 200 mg kg−1 increased photosynthesis (PN) by 50%. Furthermore, phosphorus enhanced light and nutrient use efficiency. An increase in B. excelsa dry biomass was observed when 200 mg P kg−1 was added, with maximum yield occurring at 306.2 mg P kg−1. Physiological parameters suggest robust responses by B. excelsa to P fertilization. In addition, our findings reveal the critical role of P on B. excelsa growth in Ferralsol, as well as the potential of P fertilization to improve functional traits of this important Amazonian tree.
Keywords: Ecophysiology; Functional traits; Nutrient use efficiency; Plant nutrition; Plasticity